Heat Generation by Electrical Current in a Quantum Dot Hybridized to Majorana Nanowires - Wang, Zhu-Hua (Frontiers in Physics, 2021)
Heat current generated by electronic transport through a quantum dot (QD) coupled to both a phonon bath and a Majorana nanowire hosting Majorana bound states (MBSs) is theoretically studied in the framework of nonequilibrium Green's function technique. The calculated numerical results show that electrical current can be either enhanced or suppressed by the combined influences of the phonon bath and the MBSs at certain bias voltage regimes. The enhancement and suppression of the current's magnitude for a fixed bias voltage will be reversed due to the direct hybridization between the MBSs. The simultaneous coupling between both of the two MBSs will amplify the function of the MBSs on the current, with unchanged essential the same qualitative impacts. The heat generation by the electrical current can be fully adjusted by the dot-MBSs coupling, direct hybridization between the MBSs and positions of the dot level. By properly choosing the above parameters, the heat generation can be suppressed even for increased electrical current, which is favorable in removing waste heat generated by electrical current flowing through low-dimensional circuits.